The Development of Monopoly as a Learning Medium Incorporating Visual, Auditory, and Kinesthetic Approaches to Enhance Basic Accounting Learning Outcomes at SMK Negeri 2 Jiwan - Rahayu Nur A’ini; Supri Wahyudi Utomo; Elana Era Yusdita (International journal of technology and education research, 2025)
Innovation in the learning process must be carried out in accordance with students'learning needs in order to increase learning effectiveness and make the process more meaningful, thereby maximizing the achievement of learning objectives. This study aims to develop Monopoly as a learning medium based on the VAK (Visual, Auditory, and Kinesthetic) learning styles to improve Basic Accounting learning outcomes at SMK Negeri 2 Jiwan. The research used Research and Development (R&D) method with the ADDIE development model. The Monopoly game was developed through the Genially platform and the learning implementation strategy was adapted to the VAK learning styles. The developed media underwent feasibility validation, resulting in a feasibility score of 91.25% for content aspects, 86.67% for language aspects, and 80% for media aspects. After implementation, a limited trial showed an improvement in learning outcomes, with the average pre-test score increasing from 65.2 to a post-test average of 85.8. Field test results also indicated an increase from 64.2 to 87. Thus, the development of this VAK-based Monopoly learning medium has proven effective in enhancing learning outcomes in Basic Accounting.